Pengaruh Penggunaan Jerami Padi sebagai Absorban terhadap Komposisi Kimia Silase Rumput Odot - Lola, Mario Johanes; Kleden, Markus M; Lestari, Gusti Ayu Y (Yayasan Sumber Daya Manusia Cerdas, 2024)
The research aims to determine the quality of odot grass silage which is added with rice straw as an absorbent. This research used a completely randomized design experimental method (Completely Randomized Design) consisting of 5 treatments and 3 replications. The treatments were as follows JP 0 = 100% odot grass, JP 5 = 95% odot grass + 5% rice straw, JP10 = 90 % odot grass + 10% rice straw, JP15 = 85% odot grass + 15% rice straw, JP20 = 80% odot grass + 20% rice straw. Parameters observed in this research are organic matter, crude protein, crude lipid, crude fiber and NFE. The data obtained were analyzed using Analysis of Variance (ANOVA). The result showed that NFE content was (JP0) : 34,84% (JP5): 34,80% (JP10): 33,587% (JP15): 34,41% (JP20): 33,00%; Organic matter content was (JP0): 88,84% (JP5): 88,75% (JP10): 87,76% (JP15): 88,22% (JP20): 86.71%. Crude fibre content was (JP0): 11,64% (JP5): 12,57% (JP10): 11,41% (JP15): 11,20% (JP20): 10,44%. Crude Protein content was (JP0): 14,25% (JP5): 12,38% (JP10): 13,64% (JP15): 11,27% (JP20): 12,21% and crude fibre content was (JP0): 24,07% (JP5): 24,97% (JP10): 26,06% (JP15): 27,30% (JP20): 28,12%. Statistical analysis showed that the treatment was very significant effect (P<0,01) on crude fibre content dan high significant effect (P<0,05) organic matter content but no siginificant effect (P>0,05) on crude protein, crude lipid and NFE. As a conclusion that rice straw can be used as absorbance up to 20% in silage of odot grass.